'I am frightened out of my life': Black War, white fear. (3rd April 2017) - Clements, Nicholas; Gregg, Andrew
ABSTRACT: British colonists treated Tasmanian Aborigines abominably during the early decades of the nineteenth century. Indeed, colonization resulted in the near annihilation of this ancient and unique people. Their fate, which understandably provokes feelings of sympathy and anger, has strongly influenced the literature on the 'Black War'. The Aborigines are usually portrayed as the helpless victims of ruthless, even genocidal colonists. This dichotomy, however, is a gross over-simplification. By dehumanizing colonists as heartless murderers we enter an explanatory cul-de-sac. It is only by dispassionately interrogating colonists' experiences of Aboriginal violence that we can begin to understand what precipitated this tragedy. Hence the purpose of this article, which focuses above all on the fear generated by Aboriginal violence, and the ways colonists responded to it. The essay will argue that fear – economic fear, fear for the safety of others, and fear for one's own safety – dominated the wartime experiences of frontier colonists. It will also demonstrate the influence of fear on colonists' attitudes and behaviour, as well as on the built landscape. In doing so, it covers new ground, revealing the potent anxieties of the colonizers, and the psychological impact of Aboriginal resistance.